Effectiveness Analysis of Organic and Inorganic Waste Combustion in a Household Incinerator - Lintang Surya Panuju; Adhes Gamayel; Mohamad Zaenudin (Jakarta Global University, 2026)
Waste burning is commonly practiced by communities in open areas, particularly within residential environments, often resulting in inefficient combustion and potential environmental impacts. This study aims to evaluate the combustibility of different types of household waste under open burning conditions and compare it with the performance of a proposed small-scale incinerator. The investigated waste types include wet leaf litter, dry leaf litter, food waste, plastic waste, and mixed waste, with variations in mass from 250 g, 500 g, and 750 g. Key parameters observed include combustion temperature, combustion duration, and burning behavior. The results indicate that moisture content and material composition significantly influence combustion performance. Wet leaf litter and food waste were classified as non-combustible under open burning conditions due to their high moisture content, which inhibits ignition. In contrast, dry leaf litter and plastic waste demonstrated good combustibility, achieving higher temperatures and longer combustion durations. Mixed waste exhibited moderate and inconsistent combustion characteristics due to its heterogeneous composition. In comparison, the proposed small-scale incinerator demonstrated superior performance, achieving a maximum temperature of 432°C and maintaining an operating temperature of approximately 421°C. Additionally, increasing the mass of waste generally led to longer combustion durations and, in some cases, higher temperatures. Overall, the findings highlight that open burning is less efficient for wet and mixed waste and may contribute to incomplete combustion and pollutant emissions. Therefore, pre-treatment methods such as drying and sorting, as well as the use of controlled combustion systems like incinerators, are recommended to improve combustion efficiency and reduce environmental impacts.